Development and characterisation of a recombinant Escherichia coli for the production of Polyhydroxyalkanoates - Yee, Lian Ngit (2013)
Polyhydroxyalkanoates (PHA) are biodegradable polymers synthesized by a variety of microorganisms as an intracellular carbon and energy storage materials. The nature of Escherichia coli, which is devoid of PHA-degrading enzymes, and the extensive genome studies on this microbe that can be easily manipulated and improved have led it to be a powerful host for PHA accumulation. In order to overcome the low cell density, instability of PHA production and inability of glucose uptake for wild type, Comamonas sp. EB172, a high acid-tolerant strain isolated from POME sludge in the open digester, recombinant E. coli was constructed. In this study, the unknown PHA biosynthesis genes of Comamonas sp. EB172 were successfully isolated. It was found that the isolated acetyl-CoA acetyltransferase (phaACo), acetoacetyl-CoA reductase (phaBCo) and PHA synthase, class I (phaCCo) genes were clustered together as phaCCo-phaACo-phaBCo. The modified pGEM’ vector with PHA biosynthetic genes express under the control of native promoter from Cupriavidus necator. Recombinant E. coli harbouring isolated PHA biosynthesis genes were then compared with recombinant E. coli harbouring C. necator PHA biosynthesis genes as a control in shake flask fermentation. Approximately 41% of PHA content was detected in recombinant E. coli JM109 harbouring pGEM’-phaCABCo and it was comparable to that recombinant E. coli JM109 containing phbCABRe with 46% PHA content (as a control). The effect of carbon and nitrogen on cell growth and PHA accumulation of recombinant E. coli was evaluated. The use of glucose can increase cell growth and PHA accumulation with nitrogen supplementation. However, mixed organic acids failed to increase cell growth but the PHA accumulated in the cell can be improved by supplying the nitrogen. However, E. coli JM109 transformant harbouring pGEM’-phaCABCo successfully polymerised P(3HB-co-3HV) when fed with mixed organic acids without nitrogen source. Overall,supplementation of nitrogen source in the medium improved the cell dry weight with glucose as carbon source, and increased the 3HV monomer for the polymer produced from mixed organic acids. Fed-batch fermentation not only improved the cell growth using 20 g/L glucose and 1 g/L (NH4)2SO4, but also improved the productivity using mixed organic acids for P(3HB-co-3HV) copolymer production. The productivity with 0.1 g PHA/(L.h) was achieved using 10 g/L mixed organic acids as feeding carbon source. The constant feeding of 10 g/L mixed organic acids triggered 3HV monomer formation started after 16 h and enhanced PHA content to more than 70% and P(3HB-co-3HV) copolymer with about 2 mol% 3HV monomer. The fed-batch cultivation increased the cell growth, PHA accumulation and improved the molecular weight of polymer in the range of 850 - 1490 kDa. The overall results in this study indicated that the isolated PHA biosynthesis genes from wild type bacteria can serve as PHA production system using glucose and mixed fatty acids. This finding can contribute towards the accumulation of PHA using natural or renewable carbon sources.